DOI: 10.18174/385510
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary and functional genomics study of Noccaea caerulescens, a heavy metal hyperaccumulating plant species

Abstract: An evolutionary and functional genomics study of Noccaea caerulescens, a heavy metal hyperaccumulating plant species PhD thesis, Wageningen University, Wageningen, NL (2016) With references, and summary in English

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 95 publications
(209 reference statements)
0
2
0
Order By: Relevance
“…Since the first launch of a commercial NGS platform in 2005, genome-wide expression profile approaches have been adopted in a handful of studies of N. caerulescens, such as expression arrays (Mortel et al, 2008;Plessl et al, 2005) and RNA-seq , which mainly emphasized a few well-characterised accessions such as accessions La Calamine, Lellingen, Ganges and Monte Prinzera. Whole-genome re-sequencing DNA information has been developed for a small number of accessions as well (Wang, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first launch of a commercial NGS platform in 2005, genome-wide expression profile approaches have been adopted in a handful of studies of N. caerulescens, such as expression arrays (Mortel et al, 2008;Plessl et al, 2005) and RNA-seq , which mainly emphasized a few well-characterised accessions such as accessions La Calamine, Lellingen, Ganges and Monte Prinzera. Whole-genome re-sequencing DNA information has been developed for a small number of accessions as well (Wang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This heritable intraspecific variation for metal hyperaccumulation and tolerance of N. caerulescens represents an example of local adaption in plants (Westerband et al, 2021). Gonneau et al (2014) suggested that metal-adapted populations appear to be recruited locally, for NM populations, which seems to the case for Pontaut and Vall de Varados populations as well (Wang, 2016). Unravelling the genetic basis of population differences in N. caerulescens not only enriches our understanding of plant evolutionary dynamics but also has practical implications for phytoremediation, phytomining, and biofortification of crops with essential nutrients.…”
Section: Introductionmentioning
confidence: 98%